Dupilumab dose spacing after initial successful treatment or adverse events in adult patients with atopic dermatitis: A retrospective analysis. Issue 12 (21st October 2022) - Patruno, Cataldo; Potestio, Luca; Fabbrocini, Gabriella; Napolitano, Maddalena
Abstract: Strategies on long‐term management of patients affected by atopic dermatitis (AD) undergoing treatment with dupilumab achieving good clinical response (GCR) or experiencing dupilumab‐related adverse events (AEs) are scant. Data of patients who implemented longer than scheduled dupilumab dosing interval due to GCR (at least 52 weeks of treatment and controlled AD activity [Eczema Area Severity Index ≤7 and Dermatology Life Quality Index ≤5 for at least 6 months]) or AEs (dupilumab‐related and treatment‐resistant conjunctivitis) were retrospectively collected. Dupilumab was tapered to Q3W or Q4W based on physician‐patient shared decision. At baseline (T0) and each follow‐up (week 16 [T1] and week 32 [T2]) disease severity was assessed. A total of 59 patients implemented longer than scheduled dosing interval (44 GCR, 15 AEs). Among these, 50 (35 GCR and 15 conjunctivitis) patients switched to 300 mg Q3W, while nine GCR subjects to Q4W. In the GCR group Q3W, 34 and 31 patients maintained clinical response at T1 and T2, whereas eight and seven Q4W subjects maintained clinical response at the same timepoints, respectively. No significant differences in AD severity were observed between T1 and T2 in both groups. Contrariwise, one Q3W and one Q4W patients at T1, and three Q3W and one Q4W subjects at T2, returned to dupilumab labeled dosage due to AD worsening. In conjunctivitis group, dupilumab Q3W was maintained in eight and four patients at T1 and T2, respectively. Three patients at T1 and three at T2 subjects returned to the labeled interval due to conjunctivitis remission. Four patients at T1 and four subjects at T2 interrupted dupilumab due to the persistence of conjunctivitis. A longer dupilumab dosing interval may be a valuable option in patients with a GCR and may be a useful strategy to reduce treatment‐related conjunctivitis, also with pharmacoeconomic benefit.